Latest reports of primary dysmenorrhea - Łopuszyńska, Anna Małgorzata; Pawlicki, Mateusz; Ochyra, Łukasz; Piecewicz-Szczęsna, Halina (Journal of Education, Health and Sport, 2022)
Introduction: Primary dysmenorrhea (PD) is a pelvic pain during menstruation in the absence of any pelvic pathologies. This disease mainly affects young women in reproductive age. In addition to pain, patients may experience many other symptoms including: gastrointestinal symptoms, sleep disorders. This contributes to reduction in their mental and physical quality of life. Purpose: the purpose of this review is to draw attention to a problem that affects a large number of society, is often underestimated and largely affects the quality of women's life, as well as to present the latest discoveries and reports on this issue. Material and methods: the scientific literature published in the years 2017-2022 was reviewed in the PubMed scientific database using the following keywords: primary dysmenorrhea, dysmenorrhea. Results: Increased prostaglanding levels, abnormalities in the reward system, oxidative stress, ischemia, and eotaxin may contribute to the development of pain in PD. These findings could open up new diagnostic or therapeutic targets. The first choice in the treatment of PD are NSAIDs, which are taken regularly for many years, so they must be as safe and effective as possible. Research suggests that thiaprofenic acid and ibuprofen are suitable. For alternative treatments TENS, heat, and acupuncture can be effective. Propolis, ginger, valeric acid, hops and exercise are also promising. Conclusions: PD is a varied disease that affects a large number of women. It leads to a reduction in the quality of life, hence it is necessary to conduct further research on a diverse, large group of respondents, in many centers, with the use of systematized pain scales, and lasting for a certain period of time.